Avian circovirus diseases: lessons for the study of PMWS - Todd, Daniel (Veterinary microbiology, 2004)
The diseases associated with psittacine beak and feather disease virus (BFDV), pigeon circovirus (PiCV) and goose circovirus (GoCV), which can be classified with porcine circovirus type 2 (PCV2) as members of the genus Circovirus of the family Circoviridae, have clinico-pathological features in common with post-weaning multisystemic wasting syndrome (PMWS), with which PCV2 infection is causally associated. Intracytoplasmic botryoid inclusions within macrophages and depletion of T and B lymphocytes are common histopathological features, and, in each case, affected animals usually exhibit ill-thrift and a predisposition to secondary infections, that is suggestive of an underlying immunosuppression. Although these avian diseases have been the subjects of relatively little research, their study can provide directly applicable lessons in the areas of diagnosis, epidemiology, pathogenesis and disease control for those charged with investigating PMWS. In keeping with its taxonomic separation as the only member of the genus Gyrovirus, the disease caused by chicken anaemia virus (CAV) differs histopathologically from the other circovirus-associated diseases. Most notably, the target cells of CAV have been identified as haemocytoblasts and precursor T lymphocytes, with lymphocyte depletion, which affects T cells only, occurring in cells directly infected with the virus. Nonetheless, CAV is the best-researched circovirus and provides excellent examples of both virus-induced immunosuppression and virus–virus interactions. The study of CAV-induced disease can therefore provide valuable, if less directly applicable lessons.